Challenging directions in pediatric diabetes - the place of oxidative stress and antioxidants in systemic decline - Lupu, Vasile Valeriu; Miron, Ingrith; Trandafir, Laura Mihaela; Jechel, Elena; Starcea, Iuliana Magdalena; Ioniuc, Ileana; Frasinariu, Otilia Elena; Mocanu, Adriana; Petrariu, Florin Dumitru; Danielescu, Ciprian; Nedelcu, Alin Horatiu; Salaru, Delia Lidia; et al. (Frontiers in Pharmacology, 2024)
Diabetes is a complex condition with a rising global incidence, and its impact is equally evident in pediatric practice. Regardless of whether we are dealing with type 1 or type 2 diabetes, the development of complications following the onset of the disease is inevitable. Consequently, contemporary medicine must concentrate on understanding the pathophysiological mechanisms driving systemic decline and on finding ways to address them. We are particularly interested in the effects of oxidative stress on target cells and organs, such as pancreatic islets, the retina, kidneys, and the neurological or cardiovascular systems. Our goal is to explore, using the latest data from international scientific databases, the relationship between oxidative stress and the development or persistence of systemic damage associated with diabetes in children. Additionally, we highlight the beneficial roles of antioxidants such as vitamins, minerals, polyphenols, and other bioactive molecules; in mitigating the pathogenic cascade, detailing how they intervene and their bioactive properties. As a result, our study provides a comprehensive exploration of the key aspects of the oxidative stress-antioxidants-pediatric diabetes triad, expanding understanding of their significance in various systemic diseases.